Muscle Delivery of Mitochondria-Targeted Drugs for the Treatment of Sarcopenia: Rationale and Perspectives - Francesco Bellanti; Aurelio Lo Buglio; Gianluigi Vendemiale (MDPI AG, 2022)
An impairment in mitochondrial homeostasis plays a crucial role in the process of aging and contributes to the incidence of age-related diseases, including sarcopenia, which is defined as an age-dependent loss of muscle mass and strength. Mitochondrial dysfunction exerts a negative impact on several cellular activities, including bioenergetics, metabolism, and apoptosis. In sarcopenia, mitochondria homeostasis is disrupted because of reduced oxidative phosphorylation and ATP generation, the enhanced production of reactive species, and impaired antioxidant defense. This review re-establishes the most recent evidence on mitochondrial defects that are thought to be relevant in the pathogenesis of sarcopenia and that may represent promising therapeutic targets for its prevention/treatment. Furthermore, we describe mechanisms of action and translational potential of promising mitochondria-targeted drug delivery systems, including molecules able to boost the metabolism and bioenergetics, counteract apoptosis, antioxidants to scavenge reactive species and decrease oxidative stress, and target mitophagy. Even though these mitochondria-delivered strategies demonstrate to be promising in preclinical models, their use needs to be promoted for clinical studies. Therefore, there is a compelling demand to further understand the mechanisms modulating mitochondrial homeostasis, to characterize powerful compounds that target muscle mitochondria to prevent sarcopenia in aged people.